Noninvasive Quantification of Blood Flow in Epicardial Coronary Arteries, Coronary Artery Bypass Grafts, and Anastomoses. Issue 1 (January 2017) - Ferguson, T. Bruce; Chen, Cheng; Kim, Sunghan; Jacobs, Kenneth; Peng, Zhiyong; Zhu, Zhen; Buch, Ashesh N.; Basham, Jeffery C.
Objective: Direct flow measurement in native epicardial coronary arteries, bypass conduits, and anastomoses is severely limited by the invasiveness and inaccuracy of existing technologies. As a result, less than 25% of patients undergoing coronary artery bypass grafting (CABG) worldwide have any intraoperative evaluation performed. A simple, accurate, and noninvasive technology to directly quantify blood flow and rheology surrounding anastomotic sites is a critical unmet need in CABG. Methods: Existing technology limitations drove development of a different technology solution. With an optical physics approach, flow in conduits and tissue can be quantified in real time with nonionizing broad-spectrum imaging as well as temporal and spatial analyses. Cardiac motion, calibration, and combining anatomy + physiology in imaging were challenges requiring solutions. Results: This patented imaging technology was developed and tested in an established porcine cardiac experimental model and in clinical proof-of-concept studies. Flow velocities and flows in epicardial coronary arteries vary physiologically with the cardiac cycle and with acute ischemia, as predicted by previous studies using traditional technologies. Imaging data are captured from a 30-cm viewing distance, analyzed and displayed in real time as a video. The field of view enables capture of flow in the proximal and distal epicardial coronary, the conduit, at the anastomosis and in the distal myocardium simultaneously. Conclusions: Rheologic flow interaction between conduit and native coronary at the anastomosis remains the most poorly understood technical aspect of CABG. A noninvasive, noncontact, no-risk imaging technology as simple as a snapshot can provide this critical physiologic information, validate and document intraoperative quality, and improve even further CABG outcomes.